KEPASTIAN HUKUM JAMINAN ALAT BERAT SEBAGAI OBJEK FIDUSIA - Vemil, I Kadek (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2015)
The purpose of this study was to determine how the principle of legal certainty as an effort to provide legal protection to creditors who receive heavy equipment as collateral to secure loans and how the execution of fiduciary against the heavy equipment. The approach used in this study, namely: normative juridical, which is conceived as the norm of law, rules, principles or dogmas. Juridical sociological (empirical), namely the law as a symptom of society, as a social institution or patterned behavior. The results show there has been a difficulty of the Fiduciary Receiver to execute fiduciary Fiduciary when givers are in default, as the de facto objects into an object Fiduciary it is still in control of the Borrower and fiduciary objects already in the possession of third parties that has nothing to do with the agreement.